Solvability and Admissibility of Linear Perturbed Unbounded Differential Operator Equations with Unbounded Control input Via Composite perturbation Semigroup Approach - Ali .Zboon, Radhi; Ramadhan.Kider, Jehad; Kasim .Hassan, Samir (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The perturbed linear dynamical system with unbounded perturbed control operator generating by unbounded infinitesimal generator have been adapted. The solvability of this class with admissibility as wheel as some dynamical system properties are also given and proved .The solution is guaranteed via composite perturbation semigroup approach.